Avaliação das propriedades mecânicas de compressão de ligas Ti-Si-B e Ti-Zr-Si-B - Costa, Everton Aparecido Da (2022)
The present work aims to evaluate the compressive mechanical properties of the Ti-Si-B and Ti-Zr-Si-B (with 2 at-% Zr), potentially attractive for the development of medical/dental implants, and the automotive, aeronautic and aerospace structural components. Ingots weighing close to 40 g of 97Ti-2Si-1B, 91Ti-6Si-3B, 85Ti-10Si-5B, 95Ti-2Zr-2Si-1B, 89Ti-2Zr-6Si-3B, 83Ti-2Zr-10Si-5B (%-at.) were produced by arc melting followed by heat treatment at 1200ºC for 16h in order to obtain the equilibria Ti+Ti6Si2B microstructures. The heat-treated Ti-Si-B and Ti-Zr-Si-B alloys were characterized by optical microscopy, X ray diffractometry. scanning electron microscopy, energy dispersive spectrometry, Vickers microhardness and compression tests. The average yield stress of the heat-treated 95Ti-2Zr-2Si-1B and 89Ti-2Zr-6Si-3B alloys were increased from 575,17 MPa (97Ti-2Si-1B) and 575,17 MPa (91Ti-6Si-3B) to 633,83 MPa (95Ti-2Zr-2Si-1B) and 662,67 MPa (89Ti-2Zr-6Si-3B), respectively. In contrary, the heat-treated 85Ti-10Si-5B and 83Ti-2Zr-10Si-5B alloys exhibited the average yield stress of 764,17 MPa and 722,33 MPa, respectively, suggesting to be related on non-homogeneous Ti6Si2B distribution in metal α-Ti matrix. The results obtained in the Vickers microhardness tests, indicate an increase in the alloys with 2% Zr, presenting the average values of 237 HV (97Ti-2Si-1B) to 249.9 (95Ti-2Zr-2Si-1B), of 276, 1 HV (91Ti-6Si-3B) to 278.4 HV (89Ti-2Zr-6Si-3B) and from 355.0 HV (85Ti-10Si-5B) to 364.1 HV (83Ti-2Zr-10Si-5B).